Glycerophosphocholine and Glycerophosphoethanolamine Are Not the Main Sources of the In Vivo (31)P MRS Phosphodiester Signals from Healthy Fibroglandular Breast Tissue at 7 T - van der Kemp, Wybe J. M. (Front Oncol, 2016)
PURPOSE: The identification of the phosphodiester (PDE) (31)P MR signals in the healthy human breast at ultra-high field. METHODS: In vivo (31)P MRS measurements at 7 T of the PDE signals in the breast were performed investigating the chemical shifts, the transverse- and the longitudinal relaxation times. Chemical shifts and transverse relaxation times were compared with non-ambiguous PDE signals from the liver. RESULTS: The chemical shifts of the PDE signals are shifted −0.5 ppm with respect to glycerophosphocholine (GPC) and glycerophosphoethanolamine (GPE), and the transverse and longitudinal relaxation times for these signals are a factor 3 to 4 shorter than expected for aqueous GPC and GPE. CONCLUSION: The available experimental evidence suggests that GPC and GPE are not the main source of the PDE signals measured in fibroglandular breast tissue at 7 T. These signals may predominantly originate from mobile phospholipids.